The Use of Soft System Methodology To Build A Conceptual Model for Strengthening Innovation of Entrepreneurs in Coastal Area of Jakarta - Rina Uswatun Hasanah; M. Syamsul Maarif; Nimmi Zulbainarni; M. Joko Affandi (Indonesian Journal of Business and Entrepreneurship (IJBE), 2021)
Strengthening innovation for entrepreneur is very important because nowadays consumers are smarter and they demand to meet their needs in terms of quality, renewal and price. Small businesses and beginners are often unable to achieve business sustainability. Therefore, innovative capabilities are needed to meet consumer's needs and to achieve business sustainability. By using an entrepreneurial ecosystem approach through elements of actors, factors, enthusiasm and interrelated processes that can strengthen the innovation of entrepreneur. The main purpose of this paper is to analyze the dynamics of entrepreneurial innovation so that factors to strengthen innovation can be identified. This study uses Soft System Methodology (SSM) through the application of SSM steps to obtain a conceptual model to strengthen innovation for entrepreneur. This research was conducted for 6 months, by conducting in-depth interviews with 50 respondents consisting of government, academics, community leaders and business actors. The results showed that a strong will from within the entrepreneur and the use of technology are key factors in strengthening entrepreneurial innovation. Keywords: coastal area, conceptual model, entrepreneur, innovation, soft system methodology